Internet Entrepreneurial Self-Efficacy and Sustainable Performance: A Serial Mediation Role of Social Media Usage and Innovation Capability among Micro-Entrepreneurs - Biju, Tittu Elizabath; K.V, Thomas (International Review of Management and Marketing, 2025)
Sustainable performance has become a significant objective for entrepreneurs, especially micro-entrepreneurs in emerging economies, as it facilitates enduring growth and a competitive edge. This study investigates the serial mediation effect of social media usage and innovation capability on the relationship between internet entrepreneurial self-efficacy and sustainable performance. The research employed a cross-sectional design, surveying a sample of 325 micro-entrepreneurs on online platforms. The findings indicate that social media usage and innovation capability serially mediate the link between internet entrepreneurial self-efficacy and the sustainable performance of micro-entrepreneurs in developing countries. Moreover, the serial mediation model explained 47.2% of the variance in sustainable performance. These results also contribute to the existing literature on entrepreneurship by integrating Social Cognition Theory (SCT), Resource-Based Theory (RBT), and Triple Bottom Line (TBL) into a unified framework. Additionally, the study proposes various entrepreneurial and managerial implications for improving organizational performance.